The Effectiveness of Health Education With The Booklets Method on The Level of Mother's Independence During Postpartum: Efektifitas Pendidikan Kesehatan Metode Ceramah Dengan Metode Booklet Terhadap Tingkat Kemandirian Ibu Pada Masa Nifas - S, Rika Dwi; Dinengsih, Sri; Kundaryanti, Rini (Jurnal Kebidanan Midwiferia, 2023)
Postpartum care is an important factor in improving the quality of mothers. Increased knowledge can be done by providing health education about postpartum self-care so that maternal independence can be achieved. There needs to be good cooperation between midwives in providing knowledge and motivation in meeting their needs. This study was to determine the effectiveness of health education using the lecture method with the booklet method on the level of maternal independence in postpartum care. This study used a quantitative method with a quasi-experimental research design with pretest and posttest with control group design. The research sample was all primiparous postpartum women in February 2020 which consisted of 30 people and divided into 15 people in the lecture method group and 15 people using the booklet method. The sampling technique was total sampling and the research instrument was a questionnaire. Data analysis had been done by univariate and bivariate analysis with Independent T-test. The mean values of pretest and posttest of postpartum mothers' independence in the lecture method group were 32.70 and 63.65 with standard deviations of 4.98 and 5.02. The booklet method group was 34.83 and 66.50 with standard deviations of 3.80 and 5.33. The booklet method was more effective in increasing the level of mother's independence in postpartum care with p-value = 0.035. Health education with the booklet method is more effective in increasing the level of mother's independence in postpartum care.